TEACHING AND IMPLEMENTING FUNCTION FOCUSED CARE IN ASSISTED LIVING SETTINGS. (11th November 2018) - Resnick, B; Galik, E; Boltz, M
Abstract: Residents in assisted living engage in limited amounts of physical activity and decline functionally more rapidly than their peers in nursing homes. To address this functional decline and increased time in sedentary activity a dissemination and implementation approach was used to help nursing staff integrate focused care (FFC) into routine care. Twenty-six settings across Maryland, Pennsylvania, and Massachusetts were recruited into the first cohort. A total of 274 direct care workers were exposed to education about FFC and overall they scored 87% on the FFC Knowledge Test. Direct observations using the FFC Behavior Checklist for Direct Care Workers showed that FFC was provided in 10.55 (SD=3.81) out of 19 activities and was not performed in a mean of 3.01 (SD=3.03) activities observed. FFC was least likely to be encouraged during wheelchair mobility, lower extremity bathing, range of motion activities and bladder training/toileting and should be the focus of future interventions.